P272 Impact of specialist dietitians for optimising nutrition requirements in critical care: a DGHS experience. (19th June 2022) - Nigam, Gaurav; Jones, M; Middlemiss, J; Keating, L; DeSilva, A
Abstract : Introduction: Achieving optimum quantity and balance of nutrition support (enteral or parenteral) for critically ill patients can be challenging. Specialist dietitians are often best placed to provide advice on optimal way to manage nutritional needs of critically ill patients. The Faculty of Intensive Care Medicine mandates daily dietician cover. 1 A previous UK survey study noted that only 53% respondents had a dedicated intensive care dietitian. 2 We aimed to assess the impact of specialist dietitian input on delivery of nutritional intake for patients established on enteral nutrition in critical care in a large district general hospital. Methods: Retrospective review of notes for consecutive patients during a 7-day period before and after 3-months of specialist dietitian inputs on critical care divided into two groups of 12 each. Demographic data, actual body weight (ABW), duration of critical care stay, daily calorie and protein intake for each patient was calculated. The deficit in the calorie and protein intake per patient per day was calculated based on difference between the estimated calorie and protein requirements as per ABW and the actual calories and protein delivered with the feed. The mean deficit between the pre- and post-intervention groups was then compared using an unpaired t-test. Results: The baseline characters of the two groups were comparable with mean age of 62.2 years & 56.33 years, 75% males (n=9) in both groups, mean duration of enteral nutrition on critical care of 4 days & 4.25 days and mean ABW of 82.3 kgs & 78.35 kgs in the pre- and post-intervention groups, respectively. The mean deficit in calorie intake per patient per day was 809.72 Kcal (range: -278.67 to 1760 Kcal/patient/day) and 377.16 Kcal (range: 71.20 to 1176 Kcal/patient/day) in the pre- and post-intervention groups, respectively and this difference was statistically significant (p=0.05). The mean deficit in protein intake per patient per day was 61.14 g (range: -13.93 to 104.2 g/patient/day) and 31.06 g (range: 5 to 91.50 g/patient/day) for the pre- and post-intervention groups respectively and this difference was statistically significant (p=0.02). Conclusions: We noted >50% reduction in the mean deficit for calorie and protein intake per patient per day with having regular specialist dietitian inputs on critical care after a period of 3 months. Consistent and established dietetic inputs can significantly improve the critical care teams' capacity to implement and deliver appropriate nutrition support. Further studies assessing benefits on long-term patient outcomes are warranted. 1) https://www.ficm.ac.uk/standardssafetyguidelinesstandards/guidelines-for-the-provision-of-intensive-care-services 1. Gut 2016;65: A105.